Sesquiterpene lactone variability in Parthenium hysterophorus - de la Fuente, Juana Rosa (2000)
A population of Parthenium hysterophorus collected in Salta Argentina afforded two ambrosanolides, 2β-hydroxycoronopilin and 1α,2β,4β-trihydroxypseudoguaian-6β,12-olide, as well as five known others. Plants of the fructification from those transplanted from the Puna Argentina at 1200 m over the sea level produced hymenin.